How to be ‘Green’ in Apparel Supply Chain? Proposed Model of Green Motives and Practices Relation: A Systematic Literature Review - Fauziana, Diyah Ratna (Journal of Emerging Business Management and Entrepreneurship Studies, 2025)
The growth of the apparel industry has led to an increase in waste that is disruptive to the environment, while green behavior in its supply chain still needs to be improved. This study aims to investigate the apparel supply chain’s green motives and green programs and propose a relevant model based on the result. The systematic literature review was carried out in three stages based on the PRISMA Protocol. The study obtained 409 articles from the Scopus database, and after conducting the filtering stages, 35 articles were yielded and analyzed concerning the research questions. Results showed that the green motives of the apparel supply chain are the stakeholders’ intention and requirements, government support, instability, ethical issues, collaboration partners’ requirements, environmental responsibility of the organizations, and leader commitment. Green practices in the apparel supply chain are decentralizing operations for reverse logistics, promoting circularity in business processes, eco-friendly product development, digitalization along the supply chain, green technology adoption, green advertising, green certification, green collaboration initiatives, and customer education programs. A proposed model of green motives and practices relation was developed to guide government and policymakers in formulating green strategies to promote green practices in the apparel industry.